DCEP-SE: A Dublin Core Application Profile for Experimental Software Engineering - Santana, Filipe A.; Cordeiro, André F. R.; OliveiraJr, Edson (Anais da Escola Regional de Engenharia de Software (ERES); 2025: Anais da IX Escola Regional de Engenharia de SoftwareDO - 10.5753/eres.2025.16260, 2025)
Experimental Software Engineering (ESE) faces persistent challenges in the standardization of metadata for artifacts, which limits the replication, comparison, and reuse of experimental results. Metadata provides a structured means to describe artifacts, thereby enhancing reproducibility; however, widely adopted standards such as Dublin Core (DC) may not adequately capture the specific requirements of ESE. To address this gap, this study proposes and validates DCEP-SE, a DC-based application profile tailored for documenting software engineering experiments. The profile was iteratively refined through the progressive exclusion of non-essential elements, resulting in a concise set of qualified terms aligned with experimental phases. DCEP-SE was applied to a real-world study, enabling systematic documentation of context, variables, and results. The profile enhances interoperability, promotes artifact reuse, and standardizes the reporting of ESE studies. Moreover, it provides a reusable methodological process for developing domain-specific metadata profiles in experimental software engineering.